The relationship between polychronicity and social networks: A mixed-methods study of research and development professionals. (October 2019) - Bertolotti, Fabiola; Mattarelli, Elisa; Dukerich, Janet
How do knowledge workers interact with their colleagues when organizations increasingly ask them to work on multiple activities, projects and working spheres simultaneously? Given the importance of social networks for individual and organizational success, in this study we explore the relationship between individual preferences for engaging in multiple tasks simultaneously (individual polychronicity), the perception of the organization's demands in terms of engaging in multiple tasks simultaneously (organizational polychronicity), and centrality in instrumental networks. Adopting a mixed-methods approach, we collected data from knowledge professionals in a research and development (R&D) unit. Our results show that both individual and organizational polychronicity were related to network centrality. However, the effect of individual polychronicity on instrumental network centrality was stronger, especially for advice-related interactions, suggesting that individual preferences matter more when it comes to knowledge-related interactions. Not only do we link polychronicity to a previously unexplored context, that is, social networks, but we also propose the use of a cultural toolkit perspective to explain how individuals differentially make sense of organizational temporal demands. Finally, we advance research on the antecedents of network centrality and contribute to the ongoing debate on the delicate balance between structure and individual characteristics.